2016
DOI: 10.1007/s10980-016-0382-x
|View full text |Cite
|
Sign up to set email alerts
|

Response of young and adult birds to the same environmental variables and different spatial scales during post breeding period

Abstract: Context How do young birds achieve spatial knowledge about the environment during the initial stages of their life? They may follow adults, so gaining social information and learning; alternatively, young birds may acquire knowledge of the environment themselves by experiencing habitat and landscape features. If learning is at least partially independent of adults then young birds should respond to landscape composition at finer spatial scale than adults, who possess knowledge over a larger area. Objectives We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…Hence, it seems justified to include all spatial scales which may concern studied model species, encompassing possible maximal dispersal abilities. Furthermore, our results as well as other studies considering different spatial scales indicate that bigger spatial scales matter in shaping the patterns of distribution and abundance of species [67,109,110]. …”
Section: Discussionsupporting
confidence: 84%
“…Hence, it seems justified to include all spatial scales which may concern studied model species, encompassing possible maximal dispersal abilities. Furthermore, our results as well as other studies considering different spatial scales indicate that bigger spatial scales matter in shaping the patterns of distribution and abundance of species [67,109,110]. …”
Section: Discussionsupporting
confidence: 84%
“…The juveniles of these species most probably disperse more across the landscape than those of other species and their numbers may not necessarily reflect the quality of the local habitat conditions for breeding. It is known that passerine juveniles disperse from their natal home range after birth and that dispersal behaviour might vary across species depending on the landscape composition and the learning strategies (Skórka et al ). A quantitative analysis of the link between this scale dependency observed in our results and traits such as juvenile dispersal (DeSante et al ) would provide insights into the mechanisms behind the observed pattern.…”
Section: Discussionmentioning
confidence: 99%
“…However, we do not know if wintering birds colonising are juveniles or adults (see Skórka et al, 2016 for differential response of young and adult birds to the same environmental variables). In case it is juveniles (following natal dispersal), long-term previous experience would still count if juveniles follow adults to their wintering sites.…”
Section: Discussionmentioning
confidence: 99%